Comparison of the TruView infant EVO2 PCD and C-MAC video laryngoscopes with direct Macintosh laryngoscopy for routine tracheal intubation in infants with normal airways - Haitham Mutlak; Udo Rolle; Willi Rosskopf; Richard Schalk; Kai Zacharowski; Dirk Meininger; Christian Byhahn (Clinics, 2014)
OBJECTIVE: Videolaryngoscopy has mainly been developed to facilitate difficult airway intubation. However, there is a lack of studies demonstrating this method's efficacy in pediatric patients. The aim of the present study was to compare the TruView infant EVO2 and the C-MAC videolaryngoscope with conventional direct Macintosh laryngoscopy in children with a bodyweight ≤10 kg in terms of intubation conditions and the time to intubation. METHODS: In total, 65 children with a bodyweight ≤10 kg (0-22 months) who had undergone elective surgery requiring endotracheal intubation were retrospectively analyzed. Our database was screened for intubations with the TruView infant EVO2, the C-MAC videolaryngoscope, and conventional direct Macintosh laryngoscopy. The intubation conditions, the time to intubation, and the oxygen saturation before and after intubation were monitored, and demographic data were recorded. Only children with a bodyweight ≤10 kg were included in the analysis. RESULTS: A total of 23 children were intubated using the C-MAC videolaryngoscope, and 22 children were intubated using the TruView EVO2. Additionally, 20 children were intubated using a standard Macintosh blade. The time required for tracheal intubation was significantly longer using the TruView EVO2 (52 sec vs. 28 sec for C-MAC vs. 26 sec for direct LG). However, no significant difference in oxygen saturation was found after intubation. CONCLUSION: All devices allowed excellent visualization of the vocal cords, but the time to intubation was prolonged when the TruView EVO2 was used. The absence of a decline in oxygen saturation may be due to apneic oxygenation via the TruView scope and may provide a margin of safety. In sum, the use of the TruView by a well-trained anesthetist may be an alternative for difficult airway management in pediatric patients.